Logical Querying of Relational Databases - Pistol, Luminita; BUCEA-MANEA-TONIS, Radu (Journal of Economic Development, Environment and People, 2016)
This paper aims to demonstrate the usefulness of formal logic and lambda calculus in database programming. After a short introduction in propositional and first order logic, we implement dynamically a small database and translate some SQL queries in filtered java 8 streams, enhanced with Tuples facilities from jOOλ library.